2017
DOI: 10.1590/s1519-99402017000200008
|View full text |Cite
|
Sign up to set email alerts
|

Paprika and/or marigold extracts in diets for laying hens

Abstract: SUMMARY This study was performed to evaluate the effect of the inclusion of paprika and marigold extracts in sorghum-based rations on the productivity and egg quality of laying hens. One hundred sixty laying hens were distributed in a completely randomized design in five treatments and in a factorial arrangement (2 × 2 + 1), one control ration based on corn, two levels of paprika extract (0 and 6 g/kg diet), and two levels of marigold extract (0 and 1 g/kg diet) in sorghum-based rations. There was no effect (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
6
0
2
Order By: Relevance
“…For practical use, it is necessary to analyze the price of carotenoid natural sources (Englmaierová et al, 2014). Oliveira et al (2017) worked with marigold flower extract and paprika for laying hens feed and reported that marigold flower extract in feed without paprika extract did not result in higher yolk height; however, when paprika extract were added with marigold flower extract yolk, yolk percentage was 8.34% higher because of synergistic activity of pigments resulting in better carotenoid deposition in egg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For practical use, it is necessary to analyze the price of carotenoid natural sources (Englmaierová et al, 2014). Oliveira et al (2017) worked with marigold flower extract and paprika for laying hens feed and reported that marigold flower extract in feed without paprika extract did not result in higher yolk height; however, when paprika extract were added with marigold flower extract yolk, yolk percentage was 8.34% higher because of synergistic activity of pigments resulting in better carotenoid deposition in egg.…”
Section: Resultsmentioning
confidence: 99%
“…Natural alternatives give the same coloring result when choosing eggs, without having a negative effect in egg quality and human health. As a conclusion after working with phytogenic additives for laying hens feed, Oliveira et al (2017) described that adding paprika extract inclusion in sorghum-based diets improves egg pH and yolk color. Ghasemi, Zarei, and Torki (2010) investigating garlic and thyme as phytogenic additives for laying hens, noticed that they have a benefit effect relating to higher carotenoid deposition in yolk and consequently improves yolk color.…”
Section: Resultsmentioning
confidence: 99%
“…Aderemi et al, (2013) estudando a adição de extrato de páprica e alho em dietas para galinhas de postura, verificaram que a inclusão de páprica (Capsicum annuum) aumentou a taxa de postura e a unidade Haugh. Skrivan et al, (2015) Corroborando com a presente pesquisa Oliveira et al, (2017) em seu trabalho com extrato de páprica (Capsicum annuum) e flor de marigold (Tagetes erecta) relata que não houve efeito (P> 0,05) dos tratamentos sobre o desempenho produtivo das aves.…”
Section: Resultsunclassified
“…Moeini et al, (2013) relataram que a suplementação de rações de galinhas poedeiras com aditivos carotenoides à base de pimenta vermelha (Capsicum annuum) e flor de marigold (Tagetes erecta) apresentou efeitos positivos sobre o desempenho das aves testadas. Oliveira et al, (2017) relata que a interação entre o consumo de ração foi significativa (P<0,05) para a taxa de postura, massa de ovos, cujos valores foram menores com dietas à base de sorgo sem pigmento. Garcia et al, (2009) utilizaram o pigmento natural urucum como fonte de carotenoide na dieta de galinhas poedeiras e não observaram diferença significativa no desempenho produtivo dos animais, o que corrobora com a presente pesquisa.…”
Section: Resultsunclassified
“…Another factor to consider is the use of CCOHA in sorghum-based feeds, which have low levels of carotenoids. For this reason, CCOHA may improve EYC (OLIVEIRA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%